MUSIK TRADISIONAL BAGI PERKEMBANGAN KOGNITIF ANAK USIA DINI - Firdaus Perdana (Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study discusses the music traditional for early childhood to cognitive development. Through music education of children can develop a variety of cognitive abilities, especially in the cognitive development. Based on some of theories cognitive ability in early childhood in a musical activity able to develop well because of the music, children will be interested to learn. Music is important to someone, especially children who are still happy to move freely and play. Based on the theory that music will help explain the cognitive development of children. Fact music can give a good impact on the brain development of infants and children if he hears music playing softly, rhythmically quiet and not loud.